2017
DOI: 10.1016/j.vaccine.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

MERS-CoV spike nanoparticles protect mice from MERS-CoV infection

Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) was first discovered in late 2012 and has gone on to cause over 1800 infections and 650 deaths. There are currently no approved therapeutics or vaccinations for MERS-CoV. The MERS-CoV spike (S) protein is responsible for receptor binding and virion entry to cells, is immunodominant and induces neutralizing antibodies in vivo, all of which, make the S protein an ideal target for anti-MERS-CoV vaccines. In this study, we demonstrate protection induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 19 publications
1
91
0
Order By: Relevance
“…Therefore, there has been much research on how to present effectively the main target antigen, spike protein. Previous studies have reported the effectiveness of DNA vaccines containing the spike protein gene [18,19], spike protein itself [13,17], RBD subunit vaccines [14][15][16], and viral vectors including modified vaccinia virus Ankara and adenovirus [8][9][10][11][12] for immunization of mice or nonhuman primates. Subunit vaccines, such as spike protein and RBD protein, induced neutralizing antibody against MERS-CoV, indicating the induction of a humoral immune response, and the DNA vaccine triggered the activation of cytotoxic T cells, indicating the induction of a cellular immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there has been much research on how to present effectively the main target antigen, spike protein. Previous studies have reported the effectiveness of DNA vaccines containing the spike protein gene [18,19], spike protein itself [13,17], RBD subunit vaccines [14][15][16], and viral vectors including modified vaccinia virus Ankara and adenovirus [8][9][10][11][12] for immunization of mice or nonhuman primates. Subunit vaccines, such as spike protein and RBD protein, induced neutralizing antibody against MERS-CoV, indicating the induction of a humoral immune response, and the DNA vaccine triggered the activation of cytotoxic T cells, indicating the induction of a cellular immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Although several approaches to developing a MERS-CoV vaccine have been reported, there is no clinically approved vaccine for MERS-CoV. Previous studies have investigated viral vector-based vaccines [8][9][10][11][12], subunit vaccines [13][14][15][16][17], and DNA vaccines [18,19]. Of these, vaccination using viral vectors or DNA immunization successfully generated neutralizing antibodies and protected against infection [12].…”
Section: Introductionmentioning
confidence: 99%
“…The Spike gene plays a significant role in host cell attachment and the entry of the virus in the host cells [23]. The RBD of Spike protein gene mediates the virus interaction to the host cell and binds with dipeptidyl peptidase 4 (DPP4, CD26) known as a cellular receptor which favors the viral entry into the cell and is immunodominant and induces neutralizing antibodies [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…95 Currently a variety of adjuvants have been investigated for MERS-CoV vaccines: alum, MF59, Matrix-M1, CpG, and Poly (I:C). 67,71,75,96 The use of adjuvants such as alum, CpG, and delta-inulin-based polysaccharide adjuvant has been shown to increase NAb titers and ameliorate lung eosinophilic immunopathology, 95,97 suggesting that adjuvants may be utilized in MERS-CoV vaccine development to improve immunogenicity and safety.…”
Section: Discussionmentioning
confidence: 99%
“…70 MERS-CoV S protein nanoparticles have also been developed as a possible vaccine candidate. Coleman et al 74,75 demonstrated that recombinant MERS-CoV S nanoparticles in combination with Matrix-M1 adjuvant induced NAbs, reduced lung viral titers and MERS-CoV M mRNA to baseline levels in transduced mice, suggesting that MERS-CoV replication was efficiently blocked. Matrix-M is a saponin-based adjuvant which has been shown to enhance humoral, cellular and protective responses with various pathogen vaccines including a H7N9 vaccine and Ebola virus vaccine.…”
Section: Protein Subunit Vaccinesmentioning
confidence: 99%